2020
DOI: 10.1021/acsami.0c17624
|View full text |Cite
|
Sign up to set email alerts
|

Monolithic Nanoporous Gold Foams with Catalytic Activity for Chemical Vapor Deposition Growth of Carbon Nanostructures

Abstract: While bulk gold is generally considered to be a catalytically inactive material, nanostructured forms of gold can in fact be highly catalytically active. However, few methods exist for preparing high-purity macroscopic forms of catalytically active gold. In this work, we describe the synthesis of catalytically active macroscopic nanoporous gold foams via combustion synthesis of gold bis­(tetrazolato)­amine complexes. The resulting metallically pure porous gold nanoarchitectures exhibit bulk densities of <0.1 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
(83 reference statements)
0
5
0
Order By: Relevance
“…This suggests a hierarchical porous structure of the Au gels, which is in good accordance with the scanning electron microscope (SEM) image (Figure G). Additionally, the specific surface area is determined to be 63.6 m 2 g –1 , which is much larger than those of other porous Au materials …”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…This suggests a hierarchical porous structure of the Au gels, which is in good accordance with the scanning electron microscope (SEM) image (Figure G). Additionally, the specific surface area is determined to be 63.6 m 2 g –1 , which is much larger than those of other porous Au materials …”
Section: Resultsmentioning
confidence: 86%
“…Additionally, the specific surface area is determined to be 63.6 m 2 g −1 , which is much larger than those of other porous Au materials. 34 It is well reported that noble metal aero-/hydrogels including Au showed excellent electrocatalytic activities toward small molecules. 16 This is because such gels are endowed with a metallic backbone to enable rapid electron transfer, large surface area to provide more reactivity, and high porosity to facilitate the bio-recognition immobilization and accelerate mass transfer.…”
Section: Resultsmentioning
confidence: 99%
“…For all these reasons, a single technique able to produce nanofoams with controlled properties, and different materials, is of certain interest. Various techniques have been employed for the synthesis of nanofoams, each one being usually suited for specific combinations of elements, morphologies, and average density ranges: chemical vapor deposition (CVD), [27][28][29] thermal evaporation for metallic foams, [30] sol-gel method for silica nanofoams, [31] CO 2 foaming processes [32] for polymer nanofoams, and aerosolassisted chemical vapor deposition for ceramic nanofoams. [33] Among these methods, pulsed laser deposition (PLD) stands out as a versatile and promising tool for nanofoam synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other anisotropic nanomaterials, applications of nanofoams have lagged, in part due to their synthetic and structural complexity compared to particle formulations. Nanofoams are porous nanomaterials typically created from copper [ 8 ], silver [ 9 ], or gold [ 10 , 11 ]. They are most commonly fabricated by chemical etching of biphasic mixtures of metals in the presence of strong acids that de-alloy the sample, leaving behind a porous phase [ 12 ].…”
Section: Introductionmentioning
confidence: 99%